Delineating the Benefits of Arts Education for Children’s Socioemotional Development - Holochwost, Steven J.; Goldstein, Thalia R.; Wolf, Dennie Palmer (Frontiers in Psychology, 2021)
In this paper we argue that in order for the study of arts education to continue to advance, we must delineate the effects of particular forms of arts education, offered in certain contexts, on specific domains of children’s socioemotional development. We explain why formulating precise hypotheses about the effects of arts education on children’s socioemotional development requires a differentiated definition of each arts education program or activity in question, as well as a consideration of both the immediate and broader contexts in which that program or activity occurs. We then offer the New Victory Theater’s SPARK program as an illustrative example of how these considerations allow for the refinement of hypotheses about the impact of arts education on children’s socioemotional development.